Incidence of third root in mandibular permanent first molar: An endodontic challenge - Ali M Rashid; Abdul-Haq A Suliman (University of Mosul, College of Dentistry, 2006)
Aim: To investigate the incidence and the morphology of third root for the mandibular permanent first molars from indigenous Iraqi population and their significance in the successful of endodontic treatment. Materials and Methods: A clinical, radiographical prospective evaluation of first mandibular permanent molar teeth (n= 788) and laboratory analysis of 695 extracted first mandibular permanent molars collected from University Mosul, College of Dentistry, Department of Conservative Dentistry and private dental clinic were collected and examined. All the clinical cases treated as third root present, unless otherwise both 90º, 20° mesial radiographical shift and trapezoidal access opening excluded the presence of this macrostructure. The third root was classified in three groups on the basis of the curve of the root/root canal according to Ribeiro and Consolaro (1997). Chi-square was used to determine the significance between both genders, whereas descriptive statistics was used to describe the result of observations. Results: Upon clinical and laboratory observation of total 1483 first mandibular permanent molars, 121 (8.1%) exhibited radix entomolaris (RE), 17 (14%) were classified as type I (straight root/root canal), 33 (27.2%) as type II (an initially curved entrance and the continuation as a straight root/root canals) and 71(58.6%) as type III (an initial curve in the coronal third of the root canal and a second buccally orientated curve starting from the middle to apical third). Statistical analysis with Chi-square indicated no significant differences between both genders regarding the occurrence of RE. In all cases, RE occurred bilaterally. Out of 71 teeth attended for clinic, 87.3% teeth required retreatment, while the apparent reason of extraction for 86% of 50 collected extracted teeth with RE seemed failure of endodontic treatment and the cleaning and obturation confined to the mesial and distal canals only. In all cases, the orifice of the RE was located distolingual from the main canal in the distal root. Conclusion: Clinicians should be aware of this unusual root morphology in mandibular first molars. Radiographs exposed at two different horizontal angles are needed to identify this additional root. The access cavity must be modified in a distolingual direction in order to visualize and treat the RE; this results in a trapezoidal access cavity.